ANALISIS NILAI KEKERASAN DAN STRUKTUR MIKRO PADA PENGECORAN LIMBAH PISTON BEKAS DENGAN PENAMBAHAN MATERIAL SILIKON KARBIDA (SiC) - Achmad Aziizudin; Agung Purnomo; Arbye S; Cahyo Wibi Yogiswara; Dimas Ardiansyah Halim; Setya Drana Harry Putra (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
Piston is one of the most crucial components of an engine. The primary raw material used in piston manufacturing is aluminum alloy, with silicon being the dominant element in the composition. As aluminum metal is increasingly used in modern times, its price has risen, leading to higher costs for piston components, given that aluminum is the main raw material for pistons. To address this issue, a method is needed to minimize the use of aluminum in piston manufacturing, which can be achieved by recycling used pistons and incorporating other materials, such as silicon carbide (SiC). The addition of silicon carbide (SiC) was varied at 15%, 20%, and 25%. Hardness testing results showed that the higher the SiC content, the greater the hardness value obtained. As the hardness value increases, the wear resistance of the material improves. Based on this study, the addition of 15% SiC is optimum to achieve performance equivalent to that of a new piston of brand X.